Response of electron-irradiated silicon carbide Schottky power diodes at elevated temperature - Hasbullah, Nurul Fadzlin; Mohd Khairi, Mohamad Azim; Abdullah, Yusof (Inderscience Enterprises Ltd., 2019)
Thermal dependence experiments have been carried out on silicon carbide Schottky power diodes. The devices were exposed to 3 MeV electrons with 10 MGy dose. Current density-voltage (~300 K to ~490 K) characterization have been used for the investigation. The results show that, at the highest tested temperature, the forward current density at 0.3 V increased approximately 7 orders of magnitude for unirradiated devices and approximately 8 orders of magnitude for the irradiated devices. The increase is believed due to the generation of free carriers which obtained the energy from the temperature. The series resistance of unirradiated increased with increasing temperature which may be due to the decrease in the free carrier mobility, whilst the series resistance of irradiated devices decreased with increasing temperature which indicates that more free carriers have acquired enough energy to be released from the traps introduced by the irradiation. The reverse current density shows that the current increased with increasing temperature due to the radiation-induced defects that act as generation-recombination centres. The activation energies of the irradiated devices were derived, and it is higher than the unirradiated devices. On top of that, there are two slopes in the plot of the activation energy versus voltage which suggests that the reverse leakage current is probably due to two different type of mechanisms.